Research on suspension control of maglev train via enhanced tracking differentiator - LIU Yiheng; ZHANG Hehong; LONG Zhiqiang; XIE Yunde; GU Qiuming; FU Suijin (机车电传动)
A large amount of measurement noise exists in the gap sensor signals of the suspension system of maglev train, which affects the control quality and stability of the suspension system. To address this issue, the boundary curve of the second-order discrete time optimal control was determined by means of isochronous region, and a new form of discrete time optimal control function, without complicated square root operation, was constructed based on the boundary curve and the reachable region. The phase compensation was achieved by differential prediction compensation method. Then, the suspension controller based on the new tracking differentiator (TD) was designed. The numerical simulation shows that the TD can quickly track the input signal with favorable filtering effect, no chattering and overshoots. The experiments conducted on the maglev train platform demonstrate that the proposed suspension controller of TD can significantly reduce the maximum overshoots around 15% during the levitation of the train and achieve stable suspension control of the maglev train, indicating strong engineering practicability.